The role of musical aspects of language in human cognition - Pastuszek-Lipińska, Barbara (Frontiers in Psychology, 2025)
This paper reviews musicology, linguistics, cognitive psychology, and neuroscience research on the importance of music in developing human speech and cognition. It cites research from several scientific fields on how the brain processes and reacts to melody, rhythm, harmony, loudness, dynamics and types of articulation and timbre. It also discusses musical concepts and prosodic features such as intonation, rhythm and stress related to linguistic terminology and summarises results of earlier research on how the two systems interact to strengthen or weaken an individual’s ability to function without nurturing stimulation. Music is an important preventive and therapeutic factor for human life. The author describes the interplay between music and language in the nervous system, improving or hindering communication and how it affects us personally and impacts societal mental health.